The Effect of Tophaceous Gout on the Structure and Function of the Achilles Tendon - Carroll, Matthew Richard (Auckland University of Technology, 2015)
Gout is the most prevalent form of inflammatory arthritis in men older than forty years of age and has a significant functional and social impact. Tophaceous gout is the most progressed phase of gout and is associated with foot pain, impairment and disability in joints (first metatarsophalangeal joint) and soft tissue (Achilles tendon). The structural characteristics of the Achilles tendon (AT) enables it to withstand the large forces imposed during the gait cycle. Any alteration to the internal structure of the AT may affect the ability of the gastro-soleus complex to generate force, transfer muscle power and absorb energy during the gait cycle. Current research has reported tophus deposition in the AT. However, there is limited information on the impact of tophus on the AT structure and the impact of gait characteristics in people with gout. Therefore, the aims of this thesis were to investigate the prevalence of ultrasound (US) lesions in the AT and the gait parameters of walking velocity, ankle power and ankle range of motion in participants with tophaceous gout compared to age and sex-matched control participants. Two systematic reviews with meta-analysis were also undertaken. The first systematic review was conducted on US lesions in the AT of people with inflammatory arthritis. The results demonstrated that the majority of studies reporting US lesions were in spondyloarthropathies, but limited data relating to tophaceous gout. The meta-analysis demonstrated the AT was significantly thicker in people with spondyloarthropathies, erosions more prevalent in both spondyloarthropathies and rheumatoid arthritis, but enthesophyte formation was not significantly more prevalent in participants with spondyloarthropathies when compared to control participants. The review highlighted inconsistencies in both defining and scoring US lesions indicative of inflammation and structural damage in people with inflammatory arthritis. The second systematic review evaluated gait parameters in inflammatory arthritis. The findings from the review identified the most commonly assessed gait parameters used to define gait adaptation in inflammatory arthritis, with the majority of studies focusing on gait adaptation in rheumatoid arthritis. The meta-analysis demonstrated significant differences in walking velocity, cadence, stride length, double support time, ankle power and forefoot plantar pressure, but no significant differences in ankle range of motion when participants with inflammatory arthritis were compared to controls. The review highlighted the wide range of methodologies used to acquire spatiotemporal, kinetic and plantar pressure gait parameters. Using a case-control study experimental design, AT structure was investigated using grey-scale and power Doppler US imaging. Gait function was evaluated using three-dimensional (3D) gait analysis. Twenty four participants with tophaceous gout with a mean (SD) age of 62 (12) years old were matched with 24 age and sex-matched control participants, with a mean (SD) age of 62 (12) years old. The majority of the participants were middle aged males (92%), predominately of European ethnicity (77%). The control participants demonstrated a significantly higher number of Europeans (p ≤ 0.01). Participants with gout had higher mean BMI compared to controls (p < 0.01). Participants with gout had well established disease of 17 years, with a mean serum urate level of 0.37 mmol/L. Comorbidities that included hypertension, cardiovascular disease and type 2 diabetes were found in approximately one-third of participants with tophaceous gout. The case participants with gout demonstrated had a higher prevalence of hypertension (p < 0.01) and cardiovascular disease (p = 0.03) compared to the control participants. The majority of participants with gout were prescribed allopurinol (n = 20, 83%). In order to investigate specific regions of the AT, the tendon was divided into three zones (insertion, pre-insertion and proximal to mid-section). US lesions were scored using a semi-qualitative scoring system. The scoring system assessed the tophus characteristics, tendon echogenicity, tendon vascularity, tendon morphology, enthesis, bursal morphology and bone profile using binary, continuous measurement and semi-qualitative scale. As lesions were nested within participants, a general estimating equation approach was used to analyse data. The results demonstrated participants with tophaceous gout showed a significantly higher prevalence of tophus deposition (p < 0.01), intratendinous hyperechoic spots (p < 0.01) and intratendinous inflammation (p < 0.01) throughout all zones of the AT. There was minimal data reporting hypoechoic areas with loss of fibrillar echotexture in the AT of both the case and control participants. These findings suggest that tophus deposition and associated inflammation in the AT may be a clinically silent process, with containment of inflammation. In the second case-control study, each participant undertook 3D gait analysis with passive lightweight markers used to track and model the lower limb in accordance with the Oxford Foot Model. Surface electromyography signals were recorded during gait from the medial gastrocnemius, lateral gastrocnemius and tibialis anterior of both limbs. Gait measures included walking velocity, double limb support time, first metatarsophalangeal joint motion, peak ankle joint force, ankle moment and power. When compared to control participants, participants with tophaceous gout demonstrated significantly decreased walking velocity (p < 0.01), with a mean difference of -0.20 m/s, and an increased double limb support time (p < 0.01), with a mean difference of 0.05s. Peak ankle joint power was reduced with a mean difference of -0.31 W/Kg (p = 0.01), but peak ankle joint force, difference of 15.6N (p = 0.25), and peak ankle joint moments, with a mean difference of 0.06 Nm/Kg (p = 0.16), were not significantly different between the two groups. Medial gastrocnemius (p = 0.04), with a mean difference of 2.7 %MVIC/s, and lateral gastrocnemius (p < 0.01), mean difference of 6.2 %MVIC/s muscle activity was increased in participants with tophaceous gout. Reductions in walking velocity in the cases were associated with alterations in cadence, step length, double support time and gait cycle time. Reductions in walking velocity were also associated with decreased ankle joint angular velocity in the people with gout. With the ankle joint moments preserved and not significantly different between the two groups, the reductions in ankle joint angular velocity explain the reduced ankle joint power output. These findings highlight the importance of walking velocity and imply that walking velocity may be the central mechanism by which the body modulates gait adaptation. The findings of the thesis are clinically relevant. When managing AT pathologies in people with tophaceous gout both structure and function must be considered. Structural integrity of the AT must be determined and the degree of gait adaptation must also be quantified to provide the clinician with a good overall perspective of functional ability. The findings are also relevant for the design of future clinical trials. The investigation of mechanical properties of the AT in people with gout is warranted. With baseline gait adaptations quantified, the impact of non-surgical interventions such as footwear, foot orthoses and strength training must also be considered for their ability to alter the process of gait adaptation in people with gout.
Keywords: Gout; Achilles tendon; Ultrasound imaging; Gait analysis